2018
DOI: 10.1002/csr.1483
|View full text |Cite
|
Sign up to set email alerts
|

Corporate Social Responsibility and Firm Idiosyncratic Risk in Different Market States

Abstract: This study explored the influence of corporate social responsibility (CSR) on idiosyncratic risk. Referring to an approach used by Pagan and Sossounov, we separated the sample period into up-market, down-market, and correction conditions and observed the changes in the influence of CSR on idiosyncratic risk in different market states. The results find that firms with better CSR performance can reduce their idiosyncratic risk. Furthermore, in different market states, CSR can significantly decrease idiosyncratic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
26
0
4

Year Published

2018
2018
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 51 publications
(43 citation statements)
references
References 46 publications
1
26
0
4
Order By: Relevance
“…Some empirical studies suggest that active engagement of companies in CSR activities makes them consider the interests of all stakeholders thereby supporting ERM process that also takes into account risks associated with all the stakeholders (Boatright, 2011;Godfrey et al, 2009). Prior studies have shown that better CSR performance reduces the risk level of a firm (Chen, Hung, & Lee, 2018;Cheng et al, 2012;Dhaliwal et al, 2012;Zhang et al, 2015). In this study, we employ an ERM index comprising four components, namely, strategy, operational efficiency, reporting quality, and compliance, to gauge the effectiveness of the ERM process in firms.…”
Section: Csr Erm and Firm Performancementioning
confidence: 99%
“…Some empirical studies suggest that active engagement of companies in CSR activities makes them consider the interests of all stakeholders thereby supporting ERM process that also takes into account risks associated with all the stakeholders (Boatright, 2011;Godfrey et al, 2009). Prior studies have shown that better CSR performance reduces the risk level of a firm (Chen, Hung, & Lee, 2018;Cheng et al, 2012;Dhaliwal et al, 2012;Zhang et al, 2015). In this study, we employ an ERM index comprising four components, namely, strategy, operational efficiency, reporting quality, and compliance, to gauge the effectiveness of the ERM process in firms.…”
Section: Csr Erm and Firm Performancementioning
confidence: 99%
“…However, despite suggestions that CSP and sales are related, the CSP‐sales link has remained largely untested (for a notable exception, see Lins, Servaes, & Tamayo, ). Prior studies have instead examined the effects of CSP on other important measures of performance, such as market value (Luo & Bhattacharya, ), returns on assets and equity (Testa, Miroshnychenko, Barontini, & Frey, ), corporate reputation (Melo & Garrido‐Morgado, ), idiosyncratic risk (Chen, Hung, & Lee, ), and cost of capital (Harjoto & Jo, ). Second, prior related research offers opposing predictions concerning the effect of CSP on a firm's top‐line performance.…”
Section: Introductionmentioning
confidence: 99%
“…Several studies find evidence consistent with the risk mitigation view, focusing on the cost of equity (El Ghoul, Guedhami, Kwok, & Mishra, 2011), financial risk (Bouslah, Kryzanowski, & M'Zali, 2013;Oikonomou et al, 2012), idiosyncratic risk (Chen et al, 2018), and credit risk (Attig, El Ghoul, Guedhami, & Suh, 2013;Bae et al, 2018;Ge & Liu, 2015;Jiraporn, Jiraporn, Boeprasert, & Chang, 2014;Oikonomou et al, 2014;Stellner et al, 2015).…”
Section: Literature Review and Hypothesis Developmentmentioning
confidence: 90%
“…The risk mitigation view contends that better CSP may lead to a decrease in firms' idiosyncratic risk, implying a negative relationship between CSR engagement and credit risk (Chen, Hung, & Lee, 2018).…”
Section: Literature Review and Hypothesis Developmentmentioning
confidence: 99%